Secret Revelations of Chintamani Tara : Generation and completion stage practice and commentary - Nyingpo, Pabongkha Dechen; Gonsalez, David (Somerville, USA: Wisdom Publications, 2023)
"In this book, beloved teacher Pabongkha Rinpoche shares the teachings that his teacher, Gargyi Wangpo Takphu Dorje Chang, received directly from Chittamani Tara herself. Secret Revelations of Chittamani Tara contains many profound oral instructions that are not easily found elsewhere, including one of the most powerful and practical discourses on the completion stage to be found anywhere in English translation. Rinpoche has supplemented his commentary with teachings from the Gaden Hearing Lineage as well as the general tantric teachings of the Gelug tradition. Also included are the Chittamani Tara self-generation sadhana, the ganachakra offering for Chittamani Tara, and three beautiful and moving praises and prayers to Tara composed by masters in the tradition. Lovingly translated by the scholar-monk David Gonsalez, Secret Revelations of Chittamani Tara is a guiding force leading all living beings to the state of Arya Tara. The material in this book is restricted. This book may be read only by those who have received an empowerment into any of the four classes of tantra. In order to practice this material, you must have received both the common and uncommon Chittamani Tara empowerments"--
Keywords: Religion; Buddhism; Tantra